KNOWLEDGE, ATTITUDE AND ASSOCIATED FACTORS TOWARDS HEART FAILURE MANAGEMENT AMONG NURSES WORKING IN CARDIAC UNITS - AHMAD, S; SADDIQUE , H; TASNEEM , SS (Biological and Clinical Sciences Research Journal, 2024)
Heart failure is a growing public health concern in Pakistan, with nurses playing a pivotal role in its management. Effective knowledge and attitudes among nurses are crucial for optimizing patient outcomes and reducing complications. This study aimed to assess the knowledge, attitudes, and associated factors regarding heart failure management among nurses in tertiary care hospitals. Methods: A descriptive cross-sectional study was conducted among 130 nurses working in cardiac care units and ICUs of tertiary care hospitals in Lahore, Pakistan. Participants were selected using convenience sampling. Data were collected through a validated structured questionnaire, which included demographic information, knowledge assessment, and attitudes toward heart failure management. Statistical analysis was performed using SPSS version 26, employing descriptive and inferential methods to evaluate trends and associations. Results: The majority of nurses (66.9%) correctly identified common symptoms of heart failure, such as coughing and nausea. However, gaps were observed in recognizing specific indicators, such as abdominal swelling as a sign of fluid retention (60.1%). Positive attitudes toward heart failure management were prevalent, with 58.5% strongly agreeing on the critical role of nursing care in influencing patient outcomes. Practices, such as consistent ECG monitoring (48.0%) and proper patient positioning (36.7%), were suboptimal. Significant associations were found between education level, years of experience, and competency levels (p < 0.05). Conclusion: While nurses exhibited adequate knowledge and positive attitudes toward heart failure management, significant gaps in practice adherence and specific knowledge areas were identified. Structured training programs, regular competency assessments, and evidence-based practice interventions are essential to address these deficiencies and enhance patient care in cardiac units.